2003
DOI: 10.1016/s0960-9822(03)00092-7
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Coexpression of Neural and Immune Multigene Families in Mouse Vomeronasal Sensory Neurons

Abstract: The vomeronasal organ (VNO) is a chemosensory organ specialized in the detection of pheromones in higher vertebrates. In mouse and rat, two gene superfamilies, V1r and V2r vomeronasal receptor genes, are expressed in sensory neurons whose cell bodies are located in, respectively, the apical and basal layers of the VNO epithelium. Here, we report that neurons of the basal layer express another multigene family, termed H2-Mv, representing nonclassical class I genes of the major histocompatibility complex. The ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
137
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(141 citation statements)
references
References 34 publications
2
137
1
1
Order By: Relevance
“…Others (Loconto et al, 2003) and we (Ishii et al, 2003) have shown that V2R ϩ VSNs express another multigene family, termed H2-Mv, representing nonclassical class I genes of the Mhc. Each of the nine H2-Mv genes is expressed in a subset of VSNs; individual VSNs can coexpress multiple H2-Mv genes.…”
Section: Introductionmentioning
confidence: 85%
“…Others (Loconto et al, 2003) and we (Ishii et al, 2003) have shown that V2R ϩ VSNs express another multigene family, termed H2-Mv, representing nonclassical class I genes of the Mhc. Each of the nine H2-Mv genes is expressed in a subset of VSNs; individual VSNs can coexpress multiple H2-Mv genes.…”
Section: Introductionmentioning
confidence: 85%
“…To study whether M10 and ESP families coevolve with V2Rs, we examined these families in each of the 11 vertebrates studied here. In addition to the six previously described mouse M10 genes (Ishii et al 2003;Loconto et al 2003), we identified four M10 genes in the rat. Furthermore, nine intact and 11 disrupted mouse ESP genes and five intact and three disrupted rat ESP genes were identified.…”
Section: Evolution Of Protein Families That Interact With V2rsmentioning
confidence: 98%
“…Neurons expressing V1Rs and V2Rs project to the anterior and posterior accessory olfactory bulb, respectively, where they form multiple glomeruli in spatially conserved domains (Dulac and Torello 2003). Second, most V2Rs, but not V1Rs, are coexpressed with M10 and M1 families of Major-Histocompatibility-Complex (MHC) class Ib molecules (Ishii et al 2003;Loconto et al 2003;Silvotti et al 2005). It appears that M10 proteins function as escort molecules in the transport of V2Rs (with the exception of V2R2) to the cell membrane of vomeronasal sensory neurons (Loconto et al 2003;Silvotti et al 2005).…”
mentioning
confidence: 99%
“…A third mutant showing reduced V2R sensitivity renders results consistent with the idea that these receptors are involved in detecting chemosignals that promote aggression. Thus, as discussed above, a subpopulation of the basal, V2R-expressing cells of the vomeronasal epithelium co-express nine nonclassical class I major histocompatibility complex (MHC) genes, termed H2-Mv (Ishii et al, 2003).…”
Section: Role Of the Vomeronasal And Olfactory Epithelia On Aggressionmentioning
confidence: 99%